1972
DOI: 10.1002/1097-0142(197206)29:6<1647::aid-cncr2820290632>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with mitomycin C in large infrequent doses

Abstract: One hundred and six patients (103 solid tumors, three lymphomas) were treated with large infrequent doses of mitomycin C. Thirteen patients in this group received combined radiation and chemotherapy and were evaluated separately. Most patients received 50 mg of the drug in a divided dose during the first week of treatment. After 6 weeks, maintenance injections of 10 to 30 mg of the drug were given to responsive patients at 4‐ to 6‐week intervals. Twenty‐two per cent of the patients showed a 50% reduction in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…However, after a single MMC dose, the nadir for leucopenia was evident at 3½ weeks, and for thrombocytopenia the nadir was at 4 weeks post-dosing. Crooke & Bradner (1976) also reported that anaemia was commonly seen with all treatment regimens, but this was less severe than the effects on platelets and leucocytes; similar observations were described by Godfrey & Wilbur (1972) and Montes et al (1993).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…However, after a single MMC dose, the nadir for leucopenia was evident at 3½ weeks, and for thrombocytopenia the nadir was at 4 weeks post-dosing. Crooke & Bradner (1976) also reported that anaemia was commonly seen with all treatment regimens, but this was less severe than the effects on platelets and leucocytes; similar observations were described by Godfrey & Wilbur (1972) and Montes et al (1993).…”
Section: Discussionsupporting
confidence: 64%
“…In a review of MMC toxicity, Crooke & Bradner (1976) reported that the most frequently used schedule of MMC administration was 50 mg/kg/day for 6 days and then every other day until toxicity was manifested. Crooke & Bradner (1976) also reported that anaemia was commonly seen with all treatment regimens, but this was less severe than the effects on platelets and leucocytes; similar observations were described by Godfrey & Wilbur (1972) and Montes et al (1993). However, after a single MMC dose, the nadir for leucopenia was evident at 3½ weeks, and for thrombocytopenia the nadir was at 4 weeks post-dosing.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…However, other early investigational work suggested that an intermittent dosage schedule might be less toxic as well as more efficacious in producing tumor response (15)(16)(17)(18)(19)(20). A prior study done at this institution investigated the administration of mitomycin C in large infrequent doses t o 106 patients with various types of tumor including breast (21). That study demonstrated that toxicity and therapeutic effect did not differ significantly from studies using small daily doses but that the time saved and the greater convenience to both patient and physician were considerable by using the large infrequent dosage schedule.…”
mentioning
confidence: 99%